2022
DOI: 10.3390/ijerph191610281
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequality among Fishery Workers during Climate Change: A National Population-Based and Retrospective Longitudinal Cohort Study

Abstract: Background: Owing to specific working environments, it is important to attain sustainable development goals for the health of fishery workers during climate change. Fishery workers have a hazardous working environment, leading to specific injuries and fatal events. However, limited studies have investigated the health status of fishery workers through long-term longitudinal follow-up and compared it with that of farmers and employed workers with similar socioeconomic status. Methods: The Longitudinal Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The present study indicated a high prevalence of cardiometabolic risk factors and metabolic syndrome. These findings echo those of a representative previous survey from nationwide samples that both farmers and fishery workers were more affected by cardiometabolic diseases (32). Due to an increasingly aging society, older adult people tend to have a higher risk of stroke morbidity and mortality.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study indicated a high prevalence of cardiometabolic risk factors and metabolic syndrome. These findings echo those of a representative previous survey from nationwide samples that both farmers and fishery workers were more affected by cardiometabolic diseases (32). Due to an increasingly aging society, older adult people tend to have a higher risk of stroke morbidity and mortality.…”
Section: Discussionsupporting
confidence: 86%
“…The risk factors for chronic dehydration include older age, long-term care residents, cognitive impairment, female, and use of diuretics (21,23,30). In the county of Yunlin, the proportion of older people (>65 years) ranks 3 rd among 22 counties in Taiwan with most people working in farms and fisheries; both occupations were more impacted by cardiometabolic diseases (31,32). Older adults are prone to developing dehydration with immobility, impaired thirst, and cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The current research showed that only self-esteem was likely to have an inverse relationship with QoL. Previous findings highlighted the detrimental effects of physical and mental problems towards overall well-being in aquaculture workers [ 22 , 31 , 33 , 34 ], particularly psychological distress and mental illness. Research suggested that implementing psychiatric interventions could improve self-esteem [ 56 ].…”
Section: Discussionmentioning
confidence: 48%
“…Similarly, the fatal accident rate among British fishers is 115 times greater than that of the general working population of the UK (Pougnet et al, 2013). In Taiwan, where 130,000 households, with approximately 340,000 people, are engaged in the fishery industry, Lin et al (2022) found that compared to farmers and employed workers, fishery workers were more frequently diagnosed with numerous diseases, including hypertension, diabetes, dyslipidemia, depression, peptic ulcer, chronic viral hepatitis, hepatocellular carcinoma, and total malignancy. The health of fishers in Taiwan is further threatened by the replacement of the domestic fishery industrial labor force by migrant fishing workers (Tseng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%